(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with general characteristics of speech indicators of positive and negative reaction acts. Existing classifications of negopositive acts of speech are analyzed, and new classification is suggested.